The influence of high-speed SPIV data processing parameters on aircraft wing vortex wake assessment - Garry, Kevin; Di Pasquale, Davide; Prince, Simon A.; Lawson, Nicholas J. (International Council of the Aeronautical Sciences (ICAS), 2018)
This paper uses Stereoscopic Particle Image Velocimetry (SPIV) data from the near wake of a detailed sub-scale ½ model of a representative transport aircraft wing with leading and trailing edge high lift systems and outboard aileron representation, to analyse the influence of data sampling period and frequency on the magnitude and position of the vortices resolved within the wake. The paper also evaluates the extent of vortex ‘wander’ at various stages of development within the near wake and offers guidance for optimum time-averaging strategy when investigating complex longitudinal vortex interaction studies in similar flow fields.
© The Author.